ANALISIS PENGARUH PENGELUARAN PEMERINTAH DI BIDANG PENDIDIKAN, KESEHATAN DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KOTA PAREPARE - Ladung, Fajar (Universitas Muhammadiyah Parepare, 2018)
Analysis of the Effect of Government Expenditures in the Field, Education, Health and Infrastructure on the Economic Growth of the City of Parepare